Gender as a factor in the physician and patient interaction: From service quality perspective - Versavel Tecleab Haile (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2018)
Research has not yet adequately explored the potential interplay between the physician's gender and the patient's perception of the service quality. Although various studies have covered the measurement of service quality in the hospital industry, the gender perspective has not been touched on significantly. This study is a review article that aims to explore how gender matters to the physician-patient interaction in the service setting. It discusses the patient's responses to physicians of different genders and the behavior of physicians of different genders. Consequently, it was found that gender is one of the factors that influence the physician-patient interaction and patients' perception of the doctor's competence. The gender of the physician as well as the patient could influence the communication level in medical encounters. Gender-based stereotypes in the service encounter could also affect the patient-physician interaction and the evaluations that patients give to physicians. Moreover, it was discussed that traditions, religion, culture, stereotypes and past experience serve as a foundation for customers to form a preference for the physician's sex. The relationship between the physician and the patient is shaped by many factors lying on both the patient's and the doctor's side. These factors include the difference in communication style between males and females, the patient-physician gender dyad, the difference in personality traits between males and females. All these factors fall under the service dimension that is essential in measuring the quality of service.
Keywords: M30; M31; I11; 650; gender; physician; patient; interaction; service quality; gender stereotype; communication